2021
DOI: 10.25130/tjas.21.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish weights and clove powder levels on anesthesia and recovery time in common carp Cyprinus carpio L.

Abstract: This study aimed to demonstrate how different fish weights and clove powder concentration levels together influence anesthesia and recovery time in Cyprinus carpio. Two different body weights classes of common carp (45±5g and 95±5g) were subjected to three concentrations of clove powder (200, 300 and 400mg/L) each replicated four times. At each treatment combination, the anesthetic induction and recovery times were recorded, fish held for a period of one week to two months following the experiments to assess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…[29] observed that the anesthetic effect of clove powder on (Rutilus rutilus) 7 minutes after anesthesia, at a concentration of 175, 225, 275 and 350 mg/L immediately and 24 hours after anesthesia had no effect on blood parameters, and [28] reported the same results when they used different doses of Propofol as an anesthetic agent for goldfish (Carassius auratus). While [30] observed anesthesia at concentrations of 200, 300 and 400 mg/L. The same trend in lower WBC .…”
Section: Discussionmentioning
confidence: 56%
“…[29] observed that the anesthetic effect of clove powder on (Rutilus rutilus) 7 minutes after anesthesia, at a concentration of 175, 225, 275 and 350 mg/L immediately and 24 hours after anesthesia had no effect on blood parameters, and [28] reported the same results when they used different doses of Propofol as an anesthetic agent for goldfish (Carassius auratus). While [30] observed anesthesia at concentrations of 200, 300 and 400 mg/L. The same trend in lower WBC .…”
Section: Discussionmentioning
confidence: 56%
“…The fish in each tank were euthanized with around 100ppm of clove oil at the end of the experiment, and their ultimate weight and length were recorded (Hassan et. al., 2021b).…”
Section: Plant's Source and Experimental Preparationmentioning
confidence: 99%